Summative Assessment (Written) in Undergraduate Physiology Curriculum in Bangladesh: Reflection of Educational Objective - Ali, Taskina; Begum, Noorzahan; Begum, Anjuman Ara; Shamim, Khandaker Manzare; Ferdousi, Sultana; Bennoor, Kazi Saifuddin (Journal of Bangladesh Society of Physiologist, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Background: A new curriculum for undergraduate medical education has been introduced for all universities in Bangladesh since 2002. It is expected that this new curriculum will improve the qualitative level of medical education. According to this curriculum the assessment system for the students has also been modified. This new scheme gives more emphasis on certain evaluation procedures in written examination to be customized. For example, short essay questions (SEQ) are preferred to long descriptive and short answer questions (SAQ). Questions should be specific answer oriented and targeted towards assessing the level of cognitive domain of the examinees. Objective: The present retrospective analysis was done to observe the qualitative status in the written assessment procedure in Undergraduate Physiology after the implementation of the new curriculum by comparing the setting of the different question types under new curriculum with that of the old curriculum. This study was done also to identify the areas that warrant modification. Methods: This study analyzed all new and old curriculum based written questions of the assessment examinations (except MCQ) for undergraduate Physiology course from 2001 to 2006, under 4 different universities in Bangladesh. In total 63 question papers on physiology were included for evaluation. Data were statistically analyzed by proportion test using SPSS software. Results: The analysis indicates that there are significant improvement in type of questions (SEQ, SAQ and combined) and language (specific vs. non specific) field. However improvement in all the fields of medical education was statistically insignificant. Conclusion: Therefore, it may be concluded that the question setting procedure of the written examination according to the modern assessment technique has partially fulfilled Â doi: 10.3329/jbsp.v3i0.1800 Â J Bangladesh Soc Physiol.2008 Dec;(3):61-65